Calcium-Sensing Receptor Regulates Cytosolic [Ca2+] and Plays a Major Role in the Development of Pulmonary Hypertension - Smith, Kimberly A.; Ayon, Ramon J.; Tang, Haiyang; Makino, Ayako; Yuan, Jason X.-J. (Frontiers in Physiology, 2016)
Abstract Pulmonary arterial hypertension (PAH) is a progressive disease characterized by elevated pulmonary vascular resistance (PVR) leading to right heart failure and premature death. The increased PVR results in part from pulmonary vascular remodeling and sustained pulmonary vasoconstriction. Excessive pulmonary vascular remodeling stems from increased pulmonary arterial smooth muscle cell (PASMC) proliferation and decreased PASMC apoptosis. A rise in cytosolic free Ca2+ concentration ([Ca2+]cyt) in PASMC is a major trigger for pulmonary vasoconstriction and a key stimulus for PASMC proliferation and migration, both contributing to the development of pulmonary vascular remodeling. PASMC from patients with idiopathic PAH (IPAH) have increased resting [Ca2+]cyt and enhanced Ca2+ influx. Enhanced Ca2+ entry into PASMC due to upregulation of membrane receptors and/or Ca2+ channels may contribute to PASMC contraction and proliferation and to pulmonary vasoconstriction and pulmonary vascular remodeling. We have shown that the extracellular Ca2+-sensing receptor (CaSR), which is a member of G protein-coupled receptor (GPCR) subfamily C, is upregulated and the extracellular Ca2+-induced increase in [Ca2+]cyt is enhanced in PASMC from patients with IPAH in comparison to PASMC from normal subjects. Pharmacologically blockade of CaSR significantly attenuate the development and progression of experimental pulmonary hypertension in animals. Additionally, we have demonstrated that dihydropyridine Ca2+ channel blockers (e.g., nifedipine), which are used to treat PAH patients but are only effective in 15-20% of patients, activate CaSR resulting in an increase in [Ca2+]cyt in IPAH-PASMC, but not normal PASMC. Our data indicate that CaSR functionally couples with transient receptor potential canonical (TRPC) channels to mediate extracellular Ca2+-induced Ca2+ influx and increase in [Ca2+]cyt in IPAH-PASMC. Upregulated CaSR is necessary for the enhanced extracellular Ca2+-induced increase in [Ca2+]cyt and the augmented proliferation of PASMC in patients with IPAH. This review will highlight the pathogenic role of CaSR in the development and progression of PAH.